New roles for microRNAs in cross-species communication - Liang, Hongwei (Landes Bioscience, 2013)
Communication between cells ensures coordinated behavior. In prokaryotes, this signaling is typically referred to as quorum sensing, whereas in eukaryotic cells, communication occurs through hormones. In recent years, reports have shown that small noncoding RNAs, called microRNAs (miRNAs), can be transmitted from one species to another, inducing signal interference in distant species, even in a cross-kingdom manner. This new mode of cross-species communication might mediate symbiotic and pathogenic relationships between various organisms (e.g., microorganisms and their hosts). Here, we discuss several recent studies concerning miRNA-mediated cross-species gene regulation.